Imatinib Mesylate (Glivec) in Pediatric Chronic Myelogenous Leukemia - Gholamreza Bahoush; Mardavizh Albouyeh; Parvaneh Vossough (International Journal of Hematology-Oncology and Stem Cell Research, 2009)
Introduction: Imatinib Mesylate is a selective inhibitor of TK and is considered now to be the frontline therapeutic agent during the chronic phase of CML. We have evaluated the efficacy of it on children with chronic-phase of CML. Patients and Methods: In a clinical trial study over the past 3 years, 14 patients (8 females and 6 males, 2.5-14 years old) were admitted with a diagnosis of CML. Seven patients who were in the early chronic-phase and seven who were in the late chronic-phase suffered from hematological relapse while being treated with conventional therapy. All of them had positive BCR-ABL in peripheral blood and bone marrow. Glivec was given as an oral dose of 300mg/m2/d. Then, regular monitoring was done for hematological and cytogenetic response, toxic effects, disease progression and survival. Results: All seven patients with newly- diagnosed CML and five previously treated patients attained complete and sustained hematological and cytogenetic remission in a follow-up period over 2 to 30 months (the mean was 22.5). One patient was taken off study because of drug intolerance. One patient in each group relapsed after initial response and died from progressive disease. Overall survival was 86%. No major side effects were noted and there was no drug- related mortality. Conclusion: Glivec has proved to be effective in inducing prolonged complete hematological and cytogenetic remission in newly- diagnosed as well as previously treated children with CML. One major problem is prolonged, unlimited and continued therapy which results in poor compliance as time goes by. In addition, in developing countries, high cost and suboptimal accessibility would make its routine use quite difficult.